Influence of Potting Media on Growth of Asparagus densiflorus 'Meyersii' - K Kayalvizhi (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2013)
A study was conducted on the influence of growth media on development of Asparagus densiflorus 'Meyersii' at Horticultural Research Station, Yercaud during the years 2011-12. The pot experiment was laid out under open condition, with nine set of treatments comprising various combinations of soil, sand, FYM, vermicompost and microbial consortia (Azospirillum, phosphobacteria and Pseudomonas fluorescens). From among the media combinations used, the treatment involving Soil + Sand + FYM + Vermicompost (T3) @ 2:1:1:0.5 (670g+375g+375g+165g) was found to be the best substrate for vegetative and root characters like plant height, shoot number, leaflet number, leaflet length, leaflet width, root number, root length, bulb number, bulb length, bulb width and vase-life in Asparagus densiflorus 'Meyersii'.